2012
DOI: 10.5194/acpd-12-2783-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of speciated and total mercury dry deposition at monitoring locations in Eastern and Central North America

Abstract: Dry deposition of speciated mercury, i.e., gaseous oxidized mercury (GOM), particulate bound mercury (PBM), and gaseous elemental mercury (GEM), was estimated for the year 2008–2009 at 19 monitoring locations in Eastern and Central North America. Dry deposition estimates were obtained by combining monitored 2–4 hourly speciated ambient concentration with modeled hourly dry deposition velocities (<i>V</i><sub>d</sub>) calculated using forecasted meteorology. Annual dry deposition … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 55 publications
(31 reference statements)
2
27
0
Order By: Relevance
“…The minimum detection limits for RGM and PBM of 0.46 pg/m 3 and 1.1 pg/m 3 , respectively, reported by Huang et al (2010) as three times the standard deviation of the system blanks, were used. Data from these two sites have been used in recent studies to estimate dry and total depositional Hg loadings (Zhang et al, 2012a) and evaluate predictions of speciated air concentrations from photochemical models (Baker and Bash, 2012;Zhang et al, 2012b). Although there is evidence that the Tekran instruments may underestimate ambient RGM and PBM by as much as a factor of 2-3 (e.g., Gustin et al, 2013), no attempt was made to adjust the data in any way, but we acknowledge this may be an important source of uncertainty.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…The minimum detection limits for RGM and PBM of 0.46 pg/m 3 and 1.1 pg/m 3 , respectively, reported by Huang et al (2010) as three times the standard deviation of the system blanks, were used. Data from these two sites have been used in recent studies to estimate dry and total depositional Hg loadings (Zhang et al, 2012a) and evaluate predictions of speciated air concentrations from photochemical models (Baker and Bash, 2012;Zhang et al, 2012b). Although there is evidence that the Tekran instruments may underestimate ambient RGM and PBM by as much as a factor of 2-3 (e.g., Gustin et al, 2013), no attempt was made to adjust the data in any way, but we acknowledge this may be an important source of uncertainty.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…A recent study by Zhang et al (2012b) found that between 50 and 70% of the total mercury deposition is due to GOM and PBM, although these species make up only 1% of the total gaseous mercury (TGM). GEM plays only a role for dry deposition and it needs to be considered that depending on the surface type about half of the deposited GEM is quickly re-emitted into the atmosphere (Zhang et al, 2012a). On annual average water bodies and soils can even release more GEM than is deposited, depending on deposition in the past (Bash, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Model parameters for the 'Urban' land use category were used here since the measurement site is within an urban area. Detailed description of the model and related parameters can be found in Zhang et al (2001) with modifications described by Zhang et al (2012). On-site meteorological data were not measured.…”
Section: Estimation Of Dry Deposition Fluxesmentioning
confidence: 99%